Empathy in the Prophetic Corpus: A Psychological and Narrative Examination of Shahih Hadith - Badriyah, Lailatul (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study examined the concept of empathy (ta‘āṭuf) within Islamic ethical teachings through a thematic–narrative analysis of authenticated prophetic traditions. The research aimed to clarify how empathy is constructed in the Prophet’s teachings and how these constructions intersect with contemporary psychological theories of empathetic behavior. A qualitative, library-based design was employed, drawing upon primary sources from Sahih al-Bukhari and Sahih Muslim, supported by Qur’anic exegesis, classical commentaries, and modern psychological literature. The results indicated that empathy in Islamic tradition is conceptualized through a multilayered framework encompassing emotional resonance, compassion, justice, solidarity, and collective responsibility. The well-known “one body” metaphor illustrated the believers’ interconnectedness and emphasized empathy as a moral obligation rather than a merely emotional response. The study concludes that prophetic teachings provide a holistic model of empathy that is both spiritually grounded and behaviorally actionable. This contribution enriches the broader discourse on religion and moral psychology by showing how classical Islamic ethics may inform contemporary discussions on empathy’s role in fostering compassionate and cohesive societies. Future research will benefit from comparing Islamic models of empathy with those of other religious traditions or examining how digital environments shape empathetic practices within Muslim communities.